1997
DOI: 10.1002/pro.5560060617
|View full text |Cite
|
Sign up to set email alerts
|

On the calculation of binding free energies using continuum methods: Application to MHC class I protein‐peptide interactions

Abstract: This paper describes a methodology to calculate the binding free energy (AG) of a protein-ligand complex using a continuum model of the solvent. A formal thermodynamic cycle is used to decompose the binding free energy into electrostatic and non-electrostatic contributions. In this cycle, the reactants are discharged in water, associated as purely nonpolar entities, and the final complex is then recharged. The total electrostatic free energies of the protein, the ligand, and the complex in water are calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
227
1
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(241 citation statements)
references
References 70 publications
12
227
1
1
Order By: Relevance
“…It should be noted that the uncertainty in the estimated non-electrostatic terms may be quite substantial, although it is difficult to provide their accurate estimate. For computation of non-electrostatic terms we adapted methods described by Honig and coworkers [39,10] and by Beveridge and coworkers [40]. Both groups have found that the estimated total free energies of binding were overestimated.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It should be noted that the uncertainty in the estimated non-electrostatic terms may be quite substantial, although it is difficult to provide their accurate estimate. For computation of non-electrostatic terms we adapted methods described by Honig and coworkers [39,10] and by Beveridge and coworkers [40]. Both groups have found that the estimated total free energies of binding were overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…(2) describes the electrostatic effects on binding affinity, within approximation of a single (macro)molecular conformation fixed in a given protonation state. PB calculations usually show that the electrostatic contribution to binding is unfavourable due to the large desolvation penalty of charged and polar groups which is not sufficiently compensated by the direct charge-charge interactions at the protein-ligand interface [1,10,11,12,13]. The unfavourable electrostatic contribution to the free energy of binding is usually obtained when the dielectric boundary is specified as the solvent exclusion (SE) surface along with solute dielectric constant in the range of about 2 to 4.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations